Improvement in the Synthetic Elite NT for soils with low nitrogen content. I. Genetic parameters for yield - Santos, Manoel Xavier dos (1998)
The objective of this work was to evaluate the maize (Zea mays L.), Elite Synthetic NT, selected in soils with low nitrogen availability (N-) and with male-female synchrony (ASI), and to make estimations of its genetic parameters for yield. During the 1994/95 season, 144 half-sib families were evaluated in environments with low (N-) and high (N+) nitrogen availability. The experimental design was a 12 x 12 latice with 55,000 plants/hectare. The general mean to ear weight for the families in the (N+) and (N-) environments was 4,511 and 3,237 kg of ears/ha, respectively. Yield reduction between (N+) and (N-) environments was 27.14% for the half-sib families and 65.80% for the intercalar check BR 106. The analysis of variance showed significance for treatments in both environments (P < 0.01). In (N-) the estimate for additive variance was 567.50 (g/pl)2, corresponding to 46.62% of the estimate obtained in (N+). The estimate for expected genetic progress in (N-) was of 12.78 g/pl and corresponds to 66% of the estimate found in (N+). The results indicate genetic variability and that selection in environments with nitrogen stress carried out with selection for syncrony of flowering has potential to increase efficiency in a breeding program.